Effects of contrast agents on relaxation properties of 31P metabolites. Issue 4 (8th October 2020) - Valkovič, Ladislav; Lau, Justin Y. C.; Abdesselam, Ines; Rider, Oliver J.; Frollo, Ivan; Tyler, Damian J.; Rodgers, Christopher T.; Miller, Jack J. J.
Abstract : Purpose: Phosphorous MR spectroscopy ( 31 P‐MRS) forms a powerful, non‐invasive research tool to quantify the energetics of the heart in diverse patient populations. 31 P‐MRS is frequently applied alongside other radiological examinations, many of which use various contrast agents that shorten relaxation times of water in conventional proton MR, for a better characterisation of cardiac function, or following prior computed tomography (CT). It is, however, unknown whether these agents confound 31 P‐MRS signals, for example, 2, 3‐diphosphoglycerate (2, 3‐DPG). Methods: In this work, we quantitatively assess the impact of non‐ionic, low osmolar iodinated CT contrast agent (iopamidol/Niopam), gadolinium chelates (linear gadopentetic acid dimeglumine/Magnevist and macrocyclic gadoterate meglumine/Dotarem) and superparamagnetic iron oxide nanoparticles (ferumoxytol/Feraheme) on the nuclear T1 and T2 of 31 P metabolites (ie, 2, 3‐DPG), and 1 H in water in live human blood and saline phantoms at 11.7 T. Results: Addition of all contrast agents led to significant shortening of all relaxation times in both 1 H and 31 P saline phantoms. On the contrary, the T1 relaxation time of 2, 3‐DPG in blood was significantly shortened only by Magnevist ( P = .03). Similarly, the only contrast agent that influenced the T2 relaxation times of 2, 3‐DPG in blood samples was ferumoxytol ( P = .02). Conclusion: Our results show that, unlike conventional proton MR, phosphorus MRS is unconfounded in patients who have had prior CT with contrast, not all gadolinium‐based contrast agents influence 31 P‐MRS data in vivo, and that ferumoxytol is a promising contrast agent for the reduction in 31 P‐MRS blood‐pool signal.